Diversity and spatial structure of the landscapes of the Khemchik river basin - Khovalyg, Aldynay O.; Sergey O. Ondar, Sergey N. Kirpotin, (Opción, 2019)
Now landscape researches and it results are used not only for the purpose of assessment of economic use of territories, but also at an interpretation of spatial regularities and dynamics of ecosystems.As a method, we adhere to the basic modeling approach, where the natural-territorial complexes are divided into a system of hierarchically interacting ecosystems. It can be concluded that the landscapes of the Khemchik river basin are characterized by a predominance of larch forests in the mid-mountain zone, which in turn marked as ecosystem with a high diversity and complexity of the spatial structure of the resulting terrain feature.